PENGEMBANGAN PUZZLE KEANEKARAGAMAN HAYATI VARIETAS TEBU DI PT SINERGI GULA NUSANTARA WRINGIN ANOM UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS X MA FATHUS SALAFI SITUBONDO - Moh. Sholehuddin; Nanda Eska Anugrah Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning interest of tenth-grade students at MA Fathus Salafi Situbondo in biodiversity lessons due to the limited availability of engaging, contextual, and student-centered learning media. The study aimed to determine the validity, practicality, and effectiveness of a biodiversity puzzle based on local sugarcane varieties from PT Sinergi Gula Nusantara Wringin Anom in improving students' learning interest. This research employed the Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included expert validators, a biology teacher, and tenth-grade students of MA Fathus Salafi Situbondo. Data were collected through interviews, validation sheets, practicality questionnaires, and learning interest questionnaires, and analyzed using validity and practicality percentages, normality testing, Paired Sample t-test, and N-Gain analysis. The results indicated that the developed puzzle achieved a valid to highly valid category based on expert evaluations. The practicality test showed scores of 91.23% in the small-scale trial and 80.70% in the large-scale trial, indicating that the media was practical. Furthermore, the Paired Sample t-test yielded a significance value of 0.001 (p < 0.05), while the N-Gain score reached 0.85, categorized as highly effective. Therefore, the biodiversity puzzle based on local sugarcane varieties is valid, practical, and highly effective for enhancing students' learning interest.